2005
DOI: 10.1097/01.tp.0000183959.73681.b9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Pancreatic Islets in Tolerance and Rejection

Abstract: MR imaging of iron-labeled pancreatic islets can be used for verification of the technical success of the transplantation procedure itself and for the detection of the decreasing relative islet mass due to rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 20 publications
11
93
0
Order By: Relevance
“…25,26 These studies reported discrepant results as far as the nature of the cells containing the ferumoxides is concerned: mostly endocrine cells but also some macrophages in the 1 study 25 and exclusively macrophages in the other. 26 However, they both demonstrated rapid loss of the iron-related MR signals after islet rejection. A possible explanation is the difference in the iron-handling properties of the recipient organs, ie, the heart in our study and the liver in the pancreatic islet transplantation studies.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 These studies reported discrepant results as far as the nature of the cells containing the ferumoxides is concerned: mostly endocrine cells but also some macrophages in the 1 study 25 and exclusively macrophages in the other. 26 However, they both demonstrated rapid loss of the iron-related MR signals after islet rejection. A possible explanation is the difference in the iron-handling properties of the recipient organs, ie, the heart in our study and the liver in the pancreatic islet transplantation studies.…”
Section: Discussionmentioning
confidence: 97%
“…One study (40) claimed that SPIO particles were present in lysosomes in ␤-cells of isolated rat islets. However, this claim was subsequently retracted as it appears that their technique was limited to labeling macrophages within the islet (41). Our electron microscope analysis has now clarified the location of SPIO within islet cells.…”
Section: Discussionmentioning
confidence: 98%
“…and to image them in the livers of diabetic mice using MRI (6)(7)(8)(9). One recent study showed the feasibility of this approach in T1DM patients as well (10) …”
Section: Islet Transplantation Is One Of the Most Promising Therapiesmentioning
confidence: 99%
“…Figure 7E-J), but was not detectable in nonlabeled islets (Figure 7K and L) Comparison between 7.0 T and 1. (6)(7)(8)(9)(10)23 …”
Section: Over Time Iron Uptake By Islets At 28mentioning
confidence: 99%